PENGARUH PENERAPAN GREEN ACCOUNTING DAN PERPUTARAN TOTAL ASET TERHADAP PROFITABILITAS PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA (2020-2022) - Febriani, Siti Adinda (Jurnal Ekonomi dan Bisnis (EK&BI), 2025)
This research aims to determine the effect of green accounting, measured using the performance rating of PROPER from the Ministry of Environment, and asset turnover, measured using Total Assets Turnover (TATO), on profitability, which is measured using Return on Assets (ROA) for manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2020-2022. The variables examined in this research include green accounting, total asset turnover, and profitability. This research uses a quantitative approach with secondary data, and the sample selection was conducted using a purposive sampling method, resulting in a sample of 50 companies. The data analysis techniques used in this research include descriptive statistical analysis, normality test, heteroscedasticity test, multicollinearity test, autocorrelation test, multiple linear regression analysis, hypothesis testing both partially (t-test) and simultaneously (F-test), as well as the coefficient of determination test. The results of this research indicate that the implementation of green accounting has a positive and significant effect on profitability, with a significance value of 0.014 < 0.05. Total asset turnover also has a positive and significant effect on profitability, with a significance value of 0.004 < 0.05. Simultaneously, green accounting and asset turnover have a positive and significant effect on profitability, with an Fvalue of 6.738 and a significance value of 0.003 < 0.05. The Adjusted R Square value of 0.514 indicates that 51.4% of the variability in profitability can be explained by these two variables, while the remaining 48.6% is influenced by other variables not examined in this research.